Ceramides in the skin barrier - Vávrová K.; Kováčik A.; Opálka L. (Sciendo, 2017)
The skin barrier, which is essential for human survival on dry land, is located in the uppermost skin layer, the stratum corneum. The stratum corneum consists of corneocytes surrounded by multilamellar lipid membranes that prevent excessive water loss from the body and entrance of undesired substances from the environment. To ensure this protective function, the composition and organization of the lipid membranes is highly specialized. The major skin barrier lipids are ceramides, fatty acids and cholesterol in an approximately equimolar ratio. With hundreds of molecular species of ceramide, skin barrier lipids are a highly complex mixture that complicate the investigation of its behaviour. In this minireview, the structures of the major skin barrier lipids, formation of the stratum corneum lipid membranes and their molecular organization are described.